A 4-Stage Runge-Kutta Type Method for Solution of Stiff Ordinary Differential Equations - Raihanatu Muhammad; Abdulmalik Oyedeji (Pan-American Journal of Mathematics)
In this paper, a 2 step implicit block hybrid linear multistep method was reformulated into a 4-stage block hybrid Runge-Kutta Type Method via the butcher analysis. The method can be used to solve first order stiff ordinary differential equations. A numerical example solved with the proposed method showed a better result in comparison with an existing method.